Emotions in action: Telephone‐mediated dispute resolution. (24th September 2014) - Weatherall, Ann; Stubbe, Maria
<x xml:space="preserve">Abstract</x> The present study investigated emotions as they were made visible and responded to in a particular institutional setting. Following discursive psychology the aim was to provide a rigorous account of emotion as observable in talk‐in‐interaction. Using conversation analysis a focus was on the temporality of emotion in turns of talk and over the course of an interaction. Data were recordings and transcriptions of calls to a dispute resolution service for consumers' problems with electricity and gas. The analysis identified systematic practices callers' use for describing and doing upset. Call‐takers rarely displayed emotion in the body of the calls and typically responded to institutionally relevant aspects of the callers' troubles and not the emotional ones. In the absence of any kind of endorsement of the callers' emotional stance, emotionality could escalate. Emotional affiliation regularly occurred at the end of the calls. The escalation of emotion in the absence of its endorsement and the occurrence of emotional affiliation at call‐closing evidences a sequential property of emotion that has been largely overlooked.